Episodic Liquidity Crises: Cooperative and Predatory Trading - CARLIN, BRUCE IAN; LOBO, MIGUEL SOUSA; VISWANATHAN, S. (Journal of Finance, 2007)
ABSTRACT We describe how episodic illiquidity arises from a breakdown in cooperation between market participants. We first solve a one‐period trading game in continuous‐time, using an asset pricing equation that accounts for the price impact of trading. Then, in a multi‐period framework, we describe an equilibrium in which traders cooperate most of the time through repeated interaction, providing apparent liquidity to one another. Cooperation breaks down when the stakes are high, leading to predatory trading and episodic illiquidity. Equilibrium strategies that involve cooperation across markets lead to less frequent episodic illiquidity, but cause contagion when cooperation breaks down.